2022
DOI: 10.1002/bse.2998
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities for circularity: Overcoming challenges to turn waste into a resource

Abstract: Although designing out waste is a core principle of the circular economy, in established companies, waste may not easily be designed out requiring innovation to develop alternative, value creating, uses for the waste material. This article presents a longitudinal, empirical study of the SME Rock Trade Industries, a company focused on sustainability in the quarrying sector, seeking to achieve zero waste of their extracted resource. Capabilities enabling the creation of products from the company's waste are exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
0
16
0
4
Order By: Relevance
“…Miemczyk et al (2016) underlined that there is scant research integrating dynamic capabilities and environmental strategy together, including pollution prevention, product stewardship, clean technology, and base of the pyramid (McDougall et al, 2022). Khan et al (2020) identify the microfoundations of dynamic capabilities in successful growing-circular firms moving toward CE, Elf et al (2022) in micro, small, and medium firms, while Wade et al (2022) propose a longitudinal study, which highlights their crucial relevance in 1 Teece et al (1997, p. 516) proposed the concept of dynamic capabilities as "the firm's ability to integrate, build, and reconfigure internal and external competencies to address rapidly changing environment." Teece (2007Teece ( , p. 1319 further breaks these down into the capacity to "(1) sense and shape opportunities and threats, (2) seize opportunities, and (3) maintain competitiveness through enhancing, combining, protecting, and, when necessary, reconfiguring the firm's intangible and tangible assets."…”
Section: Natural-resource-based View and Dynamic Capabilities As A Fr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Miemczyk et al (2016) underlined that there is scant research integrating dynamic capabilities and environmental strategy together, including pollution prevention, product stewardship, clean technology, and base of the pyramid (McDougall et al, 2022). Khan et al (2020) identify the microfoundations of dynamic capabilities in successful growing-circular firms moving toward CE, Elf et al (2022) in micro, small, and medium firms, while Wade et al (2022) propose a longitudinal study, which highlights their crucial relevance in 1 Teece et al (1997, p. 516) proposed the concept of dynamic capabilities as "the firm's ability to integrate, build, and reconfigure internal and external competencies to address rapidly changing environment." Teece (2007Teece ( , p. 1319 further breaks these down into the capacity to "(1) sense and shape opportunities and threats, (2) seize opportunities, and (3) maintain competitiveness through enhancing, combining, protecting, and, when necessary, reconfiguring the firm's intangible and tangible assets."…”
Section: Natural-resource-based View and Dynamic Capabilities As A Fr...mentioning
confidence: 99%
“…Miemczyk et al (2016) underlined that there is scant research integrating dynamic capabilities and environmental strategy together, including pollution prevention, product stewardship, clean technology, and base of the pyramid (McDougall et al, 2022). Khan et al (2020) identify the microfoundations of dynamic capabilities in successful growing‐circular firms moving toward CE, Elf et al (2022) in micro, small, and medium firms, while Wade et al (2022) propose a longitudinal study, which highlights their crucial relevance in innovation, experimentation, research and development, and in stakeholder connections.…”
Section: Natural‐resource‐based View and Dynamic Capabilities As A Fr...mentioning
confidence: 99%
“…In a longitudinal study of SME Rock Trade Industries, a company focused on sustainability in the quarrying industry, Wade et al (2022) analyze the company's dynamic capabilities that facilitate the utilization of its waste as a high-value resource. When the company first started reusing its waste, its dynamic capabilities were inwardly focused and linked to research, experimentation, and innovation.…”
Section: Jump-starting the Circular Economymentioning
confidence: 99%
“…Also noteworthy are the studies that showed that the adoption of technologies helps in the transition from linear economy (LE) to CE (Arroyabe et al, 2021;Belhadi et al, 2022;Lu et al, 2022;Moon & Lee, 2021;Stekelorum et al, 2021). Studies aligned with the concept of dynamic capabilities (DCs) proposed by Teece et al (1997), related to resources, routines, processes and operations, showed that these also help make the transition to CE (Cavicchi et al, 2022;Chowdhury et al, 2022;Jabbour et al, 2019;Jayarathna et al, 2022;Katz-Gerro & Sintas, 2019;Khan et al, 2021;Portillo-Tarragona et al, 2018;Scarpellini et al, 2020b;Wade et al, 2022).…”
Section: Theoretical Proposition Derived From Integrative Analysismentioning
confidence: 99%